Transformation of Islamic Political Movements in Indonesia in the Reformation Era - Yani, Ahmad (Asyahid Journal of Islamic and Quranic Studies (AJIQS), 2023)
During the New Order era, there were only 3 political parties. After the New Order ended, proposals for the formation of political parties emerged. Before the 1999 elections were held, there were 181 political parties founded by various components of the nation. Of this number, 42 of them are Islamic parties. After passing the screening stage, only 48 parties were eligible and registered as participants in the 1999 elections, of which 20 were Islamic parties. Basic facts show that an important shift has occurred in Indonesia, namely a shift from state to political society, from bureaucrats to politicians. An equally dramatic change was the emergence of the da'wah movement and political Islam as the main force that attracted attention after being on the fringes of state power for so long. This research aims to determine the characteristics of Islamic parties, the history of Islamic politics, and the transformation of Islamic politics in the Reformation era. The research results show that the initial concept of a group changes, following the flow of local politics, but in fact it is a tool to achieve its goals and mission. Joining the Islamic group does not mean forgetting or abandoning its initial goals but could be an opportunity to gain wider public sympathy for the organization's expansion. There are strong indications of the emergence of symptoms of "post-Islamism" in the Islamic movement in Indonesia as an implication of globalization. This means that the opportunity for the "post-Islamism" movement to strengthen is also quite strong in Indonesia. The main characteristic of the post-Islamism movement is their pragmatic, realistic tendency, willing to compromise with political realities that are not completely ideal and in accordance with the pure ideological scheme that they believe in and imagine. Keywords: party, political, ideological, Islam, post-Islamism.   Abstrak Pada masa Orde Baru, partai politik hanya ada 3. Setelah Orde Baru berakhir, usulan pembentukan partai politik bermunculan. Sebelum Pemilu 1999 digelar, tercatat sebanyak 181 partai politik didirikan oleh berbagai komponen bangsa. Dari jumlah tersebut, 42 di antaranya merupakan partai-partai Islam. Setelah melewati tahap penyaringan, hanya 48 partai yang berhak dan terdaftar sebagai peserta Pemilu 1999, di mana 20 di antaranya merupakan partai Islam. Fakta dasar menunjukkan bahwa terjadi pegeseran penting di Indonesia, yaitu pergeseran dari state ke political society, dari birokrat ke politisi. Perubahan yang juga dramatis adalah munculnya gerakan dakwah dan Politik Islam sebagai kekuatan pokok yang menyedot perhatian setelah sekian lama berada di pinggiran kekuasaan negara. Penelitian ini bertujuan untuk mengetahui karakteristik partai Islam, sejarah politik Islam, dan transformasi politik Islam era Reformasi. Hasil penelitian menunjukkan bahwa konsep awal suatu kelompok berubah, mengikuti alur perpolitikan lokal, tetapi sebetulnya itu adalah alat untuk mencapai tujuan dan misinya. Bergabungnya kelompok Islam tersebut bukan berarti melupakan atau meninggalkan tujuan awalnya tetapi bisa jadi sebagai ajang untuk meraih simpati masyarakat yang lebih luas demi ekspansi organisasi. Terdapat indikasi kuat munculnya gejala “post- Islamism” dalam gerakan Islam di Indonesia sebagai implikasi globalisasi. Hal ini berarti bahwa peluang menguatnya gerakan “post-Islamisme” juga cukup kuat di Indonesia. Ciri utama gerakan post-Islamisme adalah kecenderungan mereka yang pragmatis, realistis, bersedia untuk kompromi dengan realitas politik yang tak sepenuhnya ideal dan sesuai dengan skema ideologis murni yang mereka yakini dan bayangkan. Kata kunci: partai, politik, ideologis, Islam, post-Islamisme.